2016
DOI: 10.1074/jbc.m115.670257
|View full text |Cite
|
Sign up to set email alerts
|

Specific Inter-residue Interactions as Determinants of Human Monoacylglycerol Lipase Catalytic Competency

Abstract: The serine hydrolase monoacylglycerol lipase (MGL) functions as the main metabolizing enzyme of 2-arachidonoyl glycerol, an endocannabinoid signaling lipid whose elevation through genetic or pharmacological MGL ablation exerts therapeutic effects in various preclinical disease models. To inform structure-based MGL inhibitor design, we report the direct NMR detection of a reversible equilibrium between active and inactive states of human MGL (hMGL) that is slow on the NMR time scale and can be modulated in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(56 citation statements)
references
References 29 publications
3
53
0
Order By: Relevance
“…Our previous NMR-based study succeeded in isolating the open and closed states of hMGL in solution and identified one of the key residues, His-272 responsible for the conformational stability [102]. We also confirmed that the flexible nature of hMGL enables global changes in the protein structure emerging from local dynamic changes [102].…”
Section: Closer Examination Of the Crystal Structures Shows That In Tsupporting
confidence: 65%
See 4 more Smart Citations
“…Our previous NMR-based study succeeded in isolating the open and closed states of hMGL in solution and identified one of the key residues, His-272 responsible for the conformational stability [102]. We also confirmed that the flexible nature of hMGL enables global changes in the protein structure emerging from local dynamic changes [102].…”
Section: Closer Examination Of the Crystal Structures Shows That In Tsupporting
confidence: 65%
“…The downfield region of the 1D NMR spectra (11-16ppm) of hMGL displays five distinct, well-separated and characteristic peaks. In our previous study, we definitively assigned four of these downfield peaks to hydrogen-bonded histidine residues based on a site-directed mutagenesis study that substituted histidines for alanine [102]. The downfield resonances at 15.9, 14.9, 13.9 and 12.8ppm in sol hMGL are therefore ascribed to residues His103, His269, His54 and His49 respectively; whereas the peak at 11 ppm belongs to a till-date unassigned -OH hydroxyl proton.…”
Section: 32hydrogen-bonded Histidine Resonances As Natural Probes mentioning
confidence: 98%
See 3 more Smart Citations